Retrograde venography to navigate an occluded subclavian vein to achieve cardiac resynchronization therapy upgrade via His bundle pacing: a case report. Issue 2 (11th January 2023) - Pavitt, Christopher; Luther, Vishal; Lefroy, David; Tanner, Mark
Abstract: Background: Guidelines support upgrade to cardiac resynchronization therapy (CRT) through His-bundle pacing (HBP) in pacing-induced cardiomyopathy and moderate left ventricular systolic dysfunction (LVSD). Lead-related venous occlusion can represent an obstacle to upgrade procedures. We describe a technique to overcome venous occlusion through direct puncture of a collateral vein facilitating upgrade to HBP. Case summary: An 84-year-old man with a right ventricular (RV) pacemaker was referred with New York Heart Association (NYHA) Class III breathlessness secondary to moderate LVSD (left ventricular ejection fraction [LVEF] 45%). Device interrogation revealed 100% RV pacing and AV-dyssynchrony. To optimize atrioventricular (AV) and interventricular (VV) synchrony a CRT upgrade with HBP was planned. Venography revealed an occluded left subclavian vein which was probed in a retrograde manner using a 6F MPA catheter from right femoral venous access. We were able to direct the catheter distal to the left brachio-cephalic vein and define the occlusion using contrast. A collateral branch was identified, a J-wire was left in this branch and venous access was secured at this medial subclavian site using the Seldinger technique. A right atrial lead was deployed and 69 cm ISI-1 His lead was deployed via a C315 sheath at the His-bundle. The resulted in non-selective HBP (Stim-QRS end 146 ms). There were no procedural complications. Two months later both symptoms and LV function (LVEF 55%) improved. Discussion: Lead-related venous occlusion occurs frequently and can be probed in a retrograde manner from femoral venous access using contrast, facilitating direct percutaneous puncture of collateral venous branches to allow upgrade to CRT via HBP.